Computer Vision/Computer Graphics Collaboration Techniques 4th International Conference, MIRAGE 2009, Rocquencourt, France, May 4-6, 2009, Proceedings - Gagalowicz, André; Philips, Wilfried (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
This book constitutes the refereed proceedings of the 4th International Conference on Computer Vision/Computer Graphics Collaboration Techniques, MIRAGE 2009, held in Rocquencourt, France, in May 2009. The 41 revised full papers presented were carefully reviewed and selected from a total of 83 submissions. The papers cover a wide range of topics with focus on Computer Vision/Computer Graphics collaboration techniques involving image analysis/synthesis approaches especially concerning theoretical, computational, experimental or industrial aspects of model-based image analysis and image-based model synthesis.